2023
DOI: 10.1021/acsenergylett.2c02476
|View full text |Cite
|
Sign up to set email alerts
|

Gate Field Induced Extraordinary Energy Storage in MoS2-Graphene-Based Ultramicro-Electrochemical Capacitor

Abstract: On-chip microscopic energy systems have revolutionized device design for miniaturized energy storage systems. Many atomically thin materials have provided a unique opportunity to develop highly efficient small-scale devices. We report an ultramicro-electrochemical capacitor with two-dimensional (2D) molybdenum disulphide (MoS 2 ) and graphenebased electrodes. Due to the tunable density of states, 2D MoS 2 provides electric field-induced doping and, combined with a graphene interface, leads to a high carrier mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Conversely, supercapacitors offer ultrahigh power density and longer cycle life than metal-ion batteries. They operate through non-Faradic processes, electrochemical double-layer capacitors (EDLC), and the Faradic processes through reversible redox reactions in pseudocapacitors . Hybrid supercapacitors, which combine the benefits of both processes, have emerged as a solution with higher energy and power density and improved cycle life. , Various electrode materials, such as graphene, activated carbon, metal oxides, metal chalcogenides, conducting polymers, and organic frameworks, have been extensively explored for supercapacitor applications. However, designing nanostructured frameworks with high surface area, porosity, and incorporation of redox-active moieties is crucial for achieving high-performance hybrid supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, supercapacitors offer ultrahigh power density and longer cycle life than metal-ion batteries. They operate through non-Faradic processes, electrochemical double-layer capacitors (EDLC), and the Faradic processes through reversible redox reactions in pseudocapacitors . Hybrid supercapacitors, which combine the benefits of both processes, have emerged as a solution with higher energy and power density and improved cycle life. , Various electrode materials, such as graphene, activated carbon, metal oxides, metal chalcogenides, conducting polymers, and organic frameworks, have been extensively explored for supercapacitor applications. However, designing nanostructured frameworks with high surface area, porosity, and incorporation of redox-active moieties is crucial for achieving high-performance hybrid supercapacitors.…”
Section: Introductionmentioning
confidence: 99%
“…Panwar et al have reported a MoS 2 /graphene-based electrode material for ultrathin SCs. 258 They used the field effect transistor (FET) concept in their SCs. They prepared a few atomic thick layers of MoS 2 /graphene in FET-based SCs.…”
Section: Ternary Nc Ie Carbon Material/cp/mo-base...mentioning
confidence: 99%
“…Panwar et al have fabricated FET-based SCs comprised of MoS 2 /graphene. 258 They compared the electrochemical performance of ultrathin SCs with that of MoS 2 and graphene electrode material-based SCs. They observed that electrochemical performance increases almost 1000 times when combining MoS 2 /graphene.…”
Section: Ternary Nc Ie Carbon Material/cp/mo-base...mentioning
confidence: 99%
“…Further, the avenue of the electrochemical microsupercapacitor has been explored in field-effect transistor (FET) device geometries with the use of 2D materials wherein direct pen writing can simplify the fabrication process further to make customizable energy storage devices with superior performance. 27 The emerging class of layered 2D transition metal dichalcogenides remains untraversed in this domain of direct pen writing toward electronic and energy storage devices such as supercapacitors and batteries. In addition to the direct writing of 2D materials, fabricating them in the form of porous structures is also important as the aspect of nanoporosity will certainly intend to develop a potential electrode material.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extrusion-based direct ink writing of one-dimensional (1D) nanostructures such as carbon nanotubes and a variety of materials in complex 3D structures has gained significant attention for flexible conductors, circuits, sensors and actuators, soft robotics, electronic devices, and components. , Some of this acquired knowledge and applications might be easily translated to much simpler direct pen writing to enable customizable designs in the hands of the end user. Further, the avenue of the electrochemical microsupercapacitor has been explored in field-effect transistor (FET) device geometries with the use of 2D materials wherein direct pen writing can simplify the fabrication process further to make customizable energy storage devices with superior performance . The emerging class of layered 2D transition metal dichalcogenides remains untraversed in this domain of direct pen writing toward electronic and energy storage devices such as supercapacitors and batteries.…”
Section: Introductionmentioning
confidence: 99%